Patient characteristics and perceived health status of individuals with HIV and tuberculosis coinfection in Guangxi, China. Issue 14 (April 2017) - Zhu, Yujia; Wu, Jizhou; Feng, Xue; Chen, Huanhuan; Lu, Huaxiang; Chen, Li; Luo, Liuhong; Rui, Chao
Abstract : Abstract: To explore demographics, clinical and medication profiles, patients' social support, and perceived health status in HIV/TB coinfected patients in Guangxi, China. We performed a cross-sectional study in the HIV clinic of the Guigang City People's Hospital (N = 150). Health professionals conducted face-to-face interviews and collected data from patients' electronic medical records regarding patients' demographic, clinical, and medication information, as well as their social support and perceived health status. We classified all HIV/AIDS patients into HIV monoinfected and TB coinfected, at a ratio of 2:1. Compared with the HIV monoinfected, patients with HIV/TB coinfection were more likely to be older, male, less educated, unemployed, carrying health insurance, having advanced stage of HIV infection, longer history with HIV, and other opportunistic infections. Patients coinfected with TB were also more likely to hold a negative belief that their HIV treatment could prevent exacerbations, and reported significantly worse emotional/informational support, social interaction, and perceived health status. Better social support and better self-efficacy to the HIV treatment adherence was significantly associated with better perceived health status among patients with HIV and TB coinfection. Having HIV/TB coinfection was associated with poorer perceived general well-being and mental health, particularly in those undergoing TB therapy. Our findings suggest the need for mental health referrals and medication management for coinfected individuals, as well as further efforts and policies to improve coordinated care.